META—Measurement for Evolution, Transformation, and Autorealization: A New Assessment Protocol - Alessio Gori; Eleonora Topino (Behavioral Sciences, 2025)
Self-realization, a multifaceted concept, has long been a subject of interest in the scientific literature. Given its profound impact on overall well-being and work-related satisfaction, the development of instruments capturing its complexity assumes significant relevance. Therefore, this study presents the development and validation of the META—Measurement for Evolution, Transformation, and Autorealization, a self-report measure designed to assess the propensity for self-realization. The study involved a sample of 634 participants, who completed a survey comprising the META, Satisfaction with Life Scale, Career Adapt-Abilities Scale, General Self-Efficacy Scale, Insight Orientation Scale, and 10-item Connor–Davidson Resilience Scale. The analyses confirmed the statistical solidity of the three hypothesized sections; Part A (Evolutionary Thrust), including Sense of life, Spirit of service, Self-Authorizing, Self-Centering, and Internal Drive for Realization; Part B (Transformative Adaptation), including Propensity for transformation, Distress to change, Adaptability, and Fullness of the Experience; Part C (Work Attitude), including Social Service and Care, Administrative and Office Works, Entrepreneurship, Customer Service and Hospitality, and Manual activities. Factor analyses supported the structural validity of the three hypothesized sections of the META, and all subscales showed good to excellent internal consistency. Significant correlations between the META dimensions/subdimensions and self-realization or well-being outcomes also emerged. The META showed excellent psychometric properties and may be used in various fields, promoting advancements in research and practices supporting well-being and personal fulfilment.